An Analytical and Comparative Study of Methodology, Coverage, and Design in Al-Munawwir and Al-Wafi Dictionaries - Sri Wahyuni; Nur Salamah Thohiroh; Muhimmul Aulia; Mawaddatul Jannah; Uril Bahruddin (Diwan Media Pustaka, 2025)
Arabic is one of the oldest and most widely spoken languages in the world. Its significance lies not only in being the language of divine revelation and Islam but also in serving as a medium for scientific and cultural exchange among nations. However, the teaching of Arabic in Indonesia still faces several challenges, particularly the limited lexical competence of learners. This study aims to conduct a comparative analysis of two major Arabic–Indonesian dictionaries: Al-Munawwir by Ahmad Warson Munawwir and Al-Wafi by Ahmad Thaha Husain al-Mujahid and Ahmad ‘Athaillah Faṭani al-Khalil. The research employs a descriptive-analytical method with a qualitative comparative approach. Data were collected through content analysis and document studies of both dictionaries and other relevant scholarly sources. The findings reveal that Al-Munawwir adopts a traditional root-based system oriented toward classical learning, while Al-Wafi applies a modern, systematic, and multidisciplinary visual structure. The study concludes that both dictionaries play a crucial role in advancing Arabic–Indonesian lexicography and enhancing the quality of Arabic language education in academic contexts.